Eksplorasi Pentingnya Program Asistensi Mengajar terhadap Kesiapan Karir Calon Guru Madrasah Ibtidaiyah - Rohmah, Pujiati; Nurfaiza, Isrina; Nurullaika, Nurullaika; Priatmoko, Sigit (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study evaluates Teaching Assistance (AM) 's role in preparing students' careers in the Madrasah Ibtidaiyah Teacher Education (PGMI) program at UIN Malang. Using a mixed-method research design that combines quantitative and qualitative methods, this study found that AM contributes positively to students' career readiness. The questionnaires and interviews indicate that PGMI students know enough about the working world, preferred work groups, and factors influencing career choices. They have also engaged in career exploration and made appropriate career decisions, especially in choosing the teaching profession. This study highlights the importance of career planning, career exploration, and career guidance in higher education to help students prepare for entering the workforce. These findings are expected to be considered by the PGMI Study Program when designing future AM programs.